Applying knowledge and experience from potato (Solanum tuberosum) to update genetic stability data requirements in the risk assessment for vegetatively propagated biotech crops - Matthew G. Pence; Muffy Koch; Jaylee DeMond; Gary Rudgers (Frontiers in Bioengineering and Biotechnology, 2024)
Regulatory agencies require data on genetic stability as part of the safety assessment for biotech crops, even though the genetic stability of a plant is not necessarily an environmental, human or animal health safety concern. While sexual reproduction has the potential to introduce genomic variation in conventionally bred and biotech crops, vegetative propagation is genetically stable. In vegetatively propagated crops, meiosis does not occur thus limiting the number of homologous recombination events that could lead to chromosomal rearrangements in progeny plants. Genetic stability data is often, but should not be, an automatic requirement for the safety assessment of vegetatively propagated biotech crops. Genetic stability data from biotech potato events has demonstrated that vegetative propagation of potato tubers does not affect the stability of introduced DNA sequences or lead to loss of trait efficacy. The knowledge and experience gained from over 30 years of assessing the safety of biotech crops can be used by regulatory authorities to eliminate data requirements that do not address environmental, food or feed safety concerns. As a first step, regulators should consider removing requirements for genetic stability as part of the safety review for vegetatively propagated biotech crops.